2018
DOI: 10.1016/j.matlet.2017.12.084
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CuSbS2 particles with a suitable conduction band position for solar cell applications

Abstract: CuSbS 2 particles with a suitable conduction band position for solar cell applications, Materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, rising concerns over the demand and scarcity of In has driven researchers to explore alternative ternary copper chalcogenides for photovoltaic applications . An analogue to CIGS is CuSbS 2 , where Sb replaces trivalent In and Ga. CuSbS 2 has great potential for optoelectronic applications given its suitable band gap (∼1.5 eV), high absorption coefficient, and inherent p-type conductivity. Key characteristics supporting its potential as an alternative solar absorber include the following: (1) the scarcity and world demand for Sb is significantly lower than In, (2) theoretical studies suggest that CuSbS 2 is free of deep trap recombination centers that plague Cu 2 ZnSnS 4 , another attractive, earth-abundant solar absorber material, and (3) CuSbS 2 has a melting point of 551 °C, enabling low-temperature crystallization, which is ideal for low-temperature, large-scale manufacturing. , …”
Section: Introductionmentioning
confidence: 99%
“…However, rising concerns over the demand and scarcity of In has driven researchers to explore alternative ternary copper chalcogenides for photovoltaic applications . An analogue to CIGS is CuSbS 2 , where Sb replaces trivalent In and Ga. CuSbS 2 has great potential for optoelectronic applications given its suitable band gap (∼1.5 eV), high absorption coefficient, and inherent p-type conductivity. Key characteristics supporting its potential as an alternative solar absorber include the following: (1) the scarcity and world demand for Sb is significantly lower than In, (2) theoretical studies suggest that CuSbS 2 is free of deep trap recombination centers that plague Cu 2 ZnSnS 4 , another attractive, earth-abundant solar absorber material, and (3) CuSbS 2 has a melting point of 551 °C, enabling low-temperature crystallization, which is ideal for low-temperature, large-scale manufacturing. , …”
Section: Introductionmentioning
confidence: 99%
“…An et al 27 prepared CuSbS2 nanorods by a surfactant-assisted hydrothermal method. Takei et al 22 showed that CuSbS2 particles could be synthesized by a mechanochemical process, while Ikeda et al 28 , Ramasamy et al 23 , Moosakhani et al 32,33 and Yan et al 29 synthesized CuSbS2 particles by a hot-injection route. Nevertheless, the particles obtained by hydrothermal and solvothermal routes are not of as high quality as those made by a hot injection method and there is a need for more detailed studies to discover all aspects of the crystal growth and reaction mechanism for preparing CuSbS2.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, single-crystal CuSbS 2 platelets of varying thickness have been experimentally prepared using the hot injection method. , This bottom-up approach enables the synthesis of nanomaterials with well-defined size and homogeneous shape down to monolayer thickness . Interestingly, in CuSbS 2 , quantum confinement effects accompanying the nanostructuring process do not lead to a sizable increase of the optical gap, as typically observed in low-dimensional semiconductors and insulators in comparison with their bulk counterparts. For example, in transition metal dichalcogenides, spatial confinement increases absorption and photoluminescence or even induces superconductivity .…”
Section: Introductionmentioning
confidence: 99%